Project teaching: Creativity and innovation as distinctive aspects of pensamiento proyectual (ARQUISUR Revista, 2018)
This article reflects on partial results collected during research for a doctoral thesis. Proyectualidad, as a teaching object, should be revised in order to highlight pensamiento proyectual as a less explored dimension of the object. Innovation and creativity as features of pensamiento proyectual can be used to assess some of the foundations of the teaching and evaluation of proyectualidad.
Keywords: architecture; cognition; education; creative thinking; professional training